Cerebral Microbleeds Assessment and Quantification in COVID-19 Patients With Neurological Manifestations - Napolitano, Angela; Arrigoni, Alberto; Caroli, Anna; Cava, Mariangela; Remuzzi, Andrea; Longhi, Luca Giovanni; Barletta, Antonino; Zangari, Rosalia; Lorini, Ferdinando Luca; Sessa, Maria; Gerevini, Simonetta (Frontiers in Neurology, 2022)
It is increasingly acknowledged that Coronavirus Disease 2019 (COVID-19) can have neurological manifestations, and cerebral microbleeds (CMBs) have been observed in this setting. The aim of this study was to characterize CMBs patterns on Susceptibility-weighted imaging (SWI) in hospitalized COVID-19 patients with neurological manifestations. CMBs volume was quantified and correlated with clinical and laboratory parameters. The study included patients who were hospitalized due to COVID-19, exhibited neurological manifestations and underwent a brain MRI between March and May 2020. Neurological, clinical and biochemical variables were reported. The MRI was acquired using a 3T scanner, with a standardized protocol including SWI. Patients were divided based on radiological evidence of CMBs or their absence. The CMBs burden was also assessed with a semi-automatic SWI processing procedure specifically developed for the purpose of this study. Odds ratios (OR) for CMBs were calculated using age, sex, clinical and laboratory data by logistic regression analysis. Among the 1760 COVID-19 patients admitted to the ASST Papa Giovanni XXIII hospital between 1 March and 31 May 2020, 116 exhibited neurological symptoms requiring neuroimaging evaluation. Of these, 63 patients underwent brain MRI and were therefore included in the study. 14 patients had radiological evidence of CMBs (CMBs+ group). CMBs+ patients had a higher prevalence of CSF inflammation (p=0.020), a higher white blood cell count (p=0.020), and lower lymphocytes (p=0.010); the D-dimer (p=0.026), LDH (p=0.004), procalcitonin (p=0.002) and CRP concentration (p<0.001) were higher than in the CMBs- group. In multivariable logistic regression analysis, CRP (OR = 1.16, p = 0.011) indicated an association with CMBs. Estimated CMBs volume was higher in females than in males and decreased with age (Rho=-0.38; p=0.18); it was positively associated with CRP (Rho=0.36; p=0.22), and negatively associated with lymphocytes (Rho=-0.52; p=0.07). CMBs is a frequent imaging finding in hospitalized COVID-19 patients with neurological manifestations and seems to be related to pro-inflammatory status.